Development of an aircraft design expert system - Alsina, J. (Cranfield University, 1988)
The aircraft design process is characterised by the application of a wide range of knowledge across many disciplines based upon a certain degree of judgement and experience of the designer. A two pass approach has been taken towards the development of an aircraft design expert system based on the requirements of two conceptually different design steps namely, wing design and aircraft configuration. The current status of the work is one where an actual program for wing design exists with supporting documentation, and a very effective examination of the knowledge base performed based on the detail investigation of overall aircraft design process with particular emphasis on the wing design and the aircraft configuration design steps. The approach taken accomplishes the objectives of the current research in defining the knowledge base, providing tools and specifications for tools to be used within an aircraft design expert system closely following the problem-solving techniques utilised by the design expert.